Penyelesaian Tindak Pidana Pencurian Hewan Ternak Menurut Hukum Adat Masyarakat Kecamatan Alas Kota Madya Manufahi - Fernandes Vassalo, Acacio (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Theft is related to the possession of other property without the permission of the owner, with various ways and modes of operation. The role of customary law in the settlement of criminal theft (livestock) is the implementation of state duties in combating criminal acts. This is a manifestation of Article 2 paragraph (3) and Article 59 paragraph (4) of the RDTL Constitution. The application of customary law in the Alas District (Posto Administrativo) is a positive response to the high desire of the community about a peaceful and serene life in their environment. Therefore, the term law enforcement is closely related to the idea of the rule of law or legal principles as the supreme power in the rule of law and democracy in East Timor.